PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) DALAM PEMBELAJARAN ANATOMI FISIOLOGI DENGAN MEDIA KAHOOT SEBAGAI PENDUKUNG DI SMK LABSCHOOL UNESA 1 SURABAYA - Dewi Rahmawati; Nia Kusstianti; Octaverina Kecvara Pritasari; Mutimmatul Faidah (Program Studi Pendidikan Tata Rias, 2025)
The subject of Anatomy and Physiology is often considered difficult by students due to its complex terminology and less engaging teaching methods, resulting in many students scoring below the minimum competency threshold of 75. The teaching model used by educators significantly impacts learning success. Problem-Based Learning (PBL) is an effective approach, but maintaining student engagement and motivation remains a challenge. This study integrates PBL with the interactive media Kahoot to create a more engaging learning experience. The research focuses on the implementation of the PBL model, improvement in student achievement, and student responses. A pre-experimental method with a one-group pretest-posttest design was conducted on 32 Phase E TKKR students at SMK Labschool UNESA 1 Surabaya. Data were collected through cognitive tests, observations, and questionnaires. The results showed a significant improvement in student learning outcomes, with a t-value of 18.839 and a Sig. (2-tailed) value of 0.000 < 0.05. Additionally, 93% of students responded positively to the use of Kahoot, recognizing its role in enhancing interaction and providing quick feedback. Thus, the combination of PBL and Kahoot is proven to be effective in improving student learning outcomes and engagement in Anatomy and Physiology lessons. Keywords: Problem-Based Learning, Kahoot, Anatomy and Physiology, Learning Outcomes, Student Responses.